PENGARUH PENGGUNAAN MEDIA BIG BOOK DALAM PEMBELAJARAN MEMBACA UNTUK PEMULA KELAS II SD NEGERI 122399 PEMATANGSIANTAR - Maya Sinurat; Osco Parmonangan Sijabat; Minar Trisnawati Lumbantobing (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of using Big Book media in beginner reading instruction for Grade II students at SDN 122399 Pematangsiantar. The type of research used in this study is quantitative research with a pre-experimental method. Based on the results of the research and discussion conducted, it can be concluded that there is an effect of using Big Book media in beginner reading instruction for Grade II students at SDN 122399 Pematangsiantar. This is evident from the students' learning outcomes, which showed an average pretest score of 53.83, while after treatment using Big Book media, the average posttest score increased to 82.83. The t-test results showed that $t_{count} = 8.971 > t_{table} = 2.069$. Since $t_{count} > t_{table}$, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. The mean N-gain score was 29.00, classified as moderate and categorized as quite effective. Therefore, it can be concluded that the Big Book media is effective to be applied.